2011
DOI: 10.4048/jbc.2011.14.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein as Molecular Targets for Breast Cancer Therapeutics

Abstract: Recent advances in the understanding of the molecular mechanisms involved in the breast cancer development and progression have led to the identification of numerous novel molecular targets. Among these, heat shock proteins (HSPs) are being emerging molecular target due to its diverse function in cancer cells. HSPs are highly conserved molecular chaperone that are synthesized by cell in response to various stress conditions. Mammalian HSPs have been classified into several families according to their molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 81 publications
(88 reference statements)
1
36
1
1
Order By: Relevance
“…From this, it is clear that wighteone induces MCF-7 cell apoptosis in vitro and restrains cell proliferation. The activation of the AKT and MAPK pathways and the high expression of HSP90 protein are common in HER2-positive breast cancer (27) and there is a positive correlation between HSP90 and breast cancer pathological stage, local recurrence and distant metastasis, all of which result in poor patient prognosis (28). Our study reveals that wighteone blocks the expression of HSP90 protein in MCF-7 cells, and that the inhibitory effect is enhanced with increasing drug concentrations.…”
Section: A B C Dmentioning
confidence: 58%
“…From this, it is clear that wighteone induces MCF-7 cell apoptosis in vitro and restrains cell proliferation. The activation of the AKT and MAPK pathways and the high expression of HSP90 protein are common in HER2-positive breast cancer (27) and there is a positive correlation between HSP90 and breast cancer pathological stage, local recurrence and distant metastasis, all of which result in poor patient prognosis (28). Our study reveals that wighteone blocks the expression of HSP90 protein in MCF-7 cells, and that the inhibitory effect is enhanced with increasing drug concentrations.…”
Section: A B C Dmentioning
confidence: 58%
“…This concept has been evaluated in many cancers [9][10][11][12][13][14][15][16], including numerous attempts in pre-clinical and clinical breast cancer models [17][18][19][20][21][22][23][24][25][26][27] (reviewed in [28]). …”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been performed to prove the accuracy of this new strategy and "a new HSP target". Recent studies showed that HSP inhibition by using antisense oligonucleotides or inhibitors has revealed successful results in clinical trials related to cancer treatment [25][26][27][28][29][30]. Besides, several plant extracts and some natural compounds have been used to suppress HSP expression in cancer cells for a long time [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%